Kepuasan Dan Loyalitas Pelanggan Pada Produk Susu Bayi Menggunakan Service Quality Dan Path Analysis - Kukuh Winarso (Universitas Airlangga, 2010)
To enlarge market share a company has to produce quality product, accordance with what the consumers want. At the large step company has to be able to see and give more attention to the customer (consumer) satisfaction factors. In the next steps company can identify their customer loyalty to their products, that are factors or variables influence consumers loyalty to select to buy their products. There are many factors that can identify whether the consumer is loyal or not, such as by knowing the characteristics of a loyal consumer : a) buy regularly, b) buy outside the product line, c) refuse other products and show resistance from competitors power of attraction (not easily influenced by competitors power of attraction for the same products), d) recommend from mouth to mouth. Included in this research is PT. X that produce baby milk, needs approaches to identify satisfaction and finally customers loyalty. The results of this research show that consumers percieve service quality they received as not yet fulfill their expectations. Improvement priority should be started from Responsiveness, Emphaty, Assurance, Tangible and Reliability dimensions. All consumer satisfaction dimensions, both directly or simultaneously influence to consumers loyalty. Consumer satisfaction for Tangible, Reliability, Responsiveness, Assurance and Emphaty dimensions together influence to consumer loyalty of 54.66%. Whereas other variables influences outside the service quality dimension to consumer loyalty of 45.34%